Automated glycan assembly of xyloglucan oligosaccharides. Issue 1 (10th November 2015) - Dallabernardina, Pietro; Schuhmacher, Frank; Seeberger, Peter H.; Pfrengle, Fabian
Abstract : We report the automated synthesis of oligosaccharide fragments related to the hemicellulose xyloglucan based on the linear assembly of mono- and disaccharide building blocks on solid support. Abstract : We report the automated glycan assembly of oligosaccharide fragments related to the hemicellulose xyloglucan (XG). Iterative addition of monosaccharide and disaccharide building blocks to a solid support provided seven cellulose and xyloglucan fragments including XXGG- and XXXG-type oligosaccharides.